Tackling social anxiety with targeted brain stimulation: investigating the effects of transcranial static magnetic field stimulation on self-focused attention - Tomita, Nozomi; Katayama, Hiroki; Kurihara, Yuto; Takahashi, Toru; Shibata, Sumiya; Mima, Tatsuya; Osu, Rieko; Kumano, Hiroaki (Frontiers in Behavioral Neuroscience, 2024)
Previous studies suggested that self-focused attention (SFA), implicated in social anxiety disorder (SAD), correlates with heightened activity in the right frontopolar area (rFPA), which is the right prefrontal cortex just behind the forehead. Transcranial static magnetic field stimulation (tSMS) is a non-invasive brain stimulation method capable of temporarily suppressing brain function beneath the magnet. We explored whether tSMS on individuals with tendencies toward SAD elicited (1) suppressing rFPA activation during the resting-state and (2) reducing SFA during a subsequent speech task. Twenty-three university students with social anxiety performed two speech tasks. Between tasks, the tSMS group received neodymium magnet stimulation while the sham group received fake magnet stimulation on the rFPA for 20 min. Resting-state rFPA activities was measured using functional nearinfrared spectroscopy (fNIRS), while SFA (body sensations and observer perspective), field perspective, and detached mindfulness (DM) perspective were assessed via questionnaires during both speech tasks. The observer perspective means SFA to self-imagery from others' viewpoint, while the field and DM perspectives mean appropriately focusing on the external environment. The results indicated that tSMS intervention decreased rFPA activity from pre-to post-intervention rest. Then, tSMS reduced SFA to bodily sensations and increased DM perspective from pre-to post-intervention speech, especially in those with high levels of social anxiety. Furthermore, tSMS enhanced the field perspective regardless of social anxiety tendency. The results suggest that tSMS may suppress overactivity in rFPA, reduce SFA to body sensation, and increase adaptive attention in highly socially anxious individuals. Our study suggests the possibility of the clinical application of tSMS for treating SAD.